Boba Fett is dead - Taylor, Tom, 1978- (Star wars, blood ties, 2013)
"Boba Fett, the galaxy's most feared bounty hunter, is dead. But members of the team that killed Fett are themselves being picked off one by one by a mysterious avenger"--